Melatonin Relieves Ozone Stress in Grape Leaves by Inhibiting Ethylene Biosynthesis - Liu, Chuang; Kang, Hui; Wang, Yafang; Yao, Yuxin; Gao, Zhen; Du, Yuanpeng (Frontiers in Plant Science, 2021)
Ozone (O3) stress severely affects the normal growth of grape leaves. Melatonin (MT) plays a significant role in plant response to various abiotic stresses, but its role in O3 stress and related mechanisms are poorly understood. Transcriptome analysis showed that carbohydrate metabolism was the most enriched biological process in ‘Cabernet Sauvignon’ grapes under O3 and MT treatment. O3 stress upregulated the expression of genes related to ethylene synthesis and signal transduction, while MT treatment significantly inhibited the ethylene response mediated by O3 stress. Further experiments showed that both MT and aminovinylglycine (AVG, an inhibitor of ethylene synthesis) improved the photosynthetic and antioxidant capacities of grape leaves under O₃ stress, while ethephon had the opposite effect. The combined treatment effect of MT and ethylene inhibitor was similar to that of MT alone. Exogenous MT reduced ethylene production in grape leaves under O3 stress, while ethephon and ethylene inhibitors had little effect on the MT content of grape leaves after O3 stress. However, overexpression of VvACO2 in grape leaves endogenously induced ethylene synthesis and aggravated O3 stress. Overexpression of the MT synthesis gene VvASMT in tobacco alleviated O3 stress and reduced ethylene synthesis after O3 stress. In summary, MT can alleviate O3 stress in grape leaves by inhibiting ethylene synthesis.